2022
DOI: 10.55493/5002.v12i7.4555
|View full text |Cite
|
Sign up to set email alerts
|

The Triangular Causal Relationship between Economic Growth, Tourism, and Foreign Direct Investment: A Case Study in Central Vietnam

Abstract: The article proposes a method to broach the complication and mixture of the triangular causal nexus among gross domestic product (GDP), foreign direct investment (FDI), and foreign tourist arrivals (FTA) in Thua Thien Hue (TTH) province that has not yet been studied. FDI into TTH province fluctuates unpredictably, so the study investigates the causal relationship between the triangular variables over the whole period (1995–2019) and the shortened period (2003–2019). The ARDL model is the most optimal choice du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Very few studies assess the interaction between tourism demand and macroeconomic variables in Vietnam. The limited studies include Selvanathan et al (2021), Puah et al (2019), Ngo & Ha (2022), and Le, Nguyen, and Tran (2022). In particular, Selvanathan et al (2021) explain why Vietnam is a favorite destination using exchange rate variables and commodity price differentials between Vietnam and other countries.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies assess the interaction between tourism demand and macroeconomic variables in Vietnam. The limited studies include Selvanathan et al (2021), Puah et al (2019), Ngo & Ha (2022), and Le, Nguyen, and Tran (2022). In particular, Selvanathan et al (2021) explain why Vietnam is a favorite destination using exchange rate variables and commodity price differentials between Vietnam and other countries.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…They find a positive and robust interaction between tourism demand, economic growth, and the real exchange rate. A study by Le et al (2022) evaluates the triangular causal relationship between economic growth, tourism, and economic growth in central Vietnam and finds that there are two-way short-and long-term causal interactions between foreign tourist arrival and economic growth. Although the previous studies have used macroeconomic variables as determinants of tourism demand for Vietnam, none of them has accounted for trade as a determinant of tourism demand in Vietnam.…”
Section: Empirical Reviewmentioning
confidence: 99%
“…The need for facilitating FDI is in light of the developmental prospects they bring. As opposed to the old paradigm that emphasised FDI attraction on the principle of quantity, the new approach looks at the quality dimension of foreign investors [53]. Notably, the quality dimension is largely underpinned by the sustainability orientation of foreign investors towards host communities as influenced by host IFAs.…”
Section: The Policy and Legislative Interface: Las Fdi Facilitation A...mentioning
confidence: 99%
“…In contrast, the bottom-up approach to development in Namibia has been embraced in several legislations (that is, Decentralisation Policy, Vision 2030 and the National Development Plans (NDPs); the Namibian government has decentralised FDI facilitation but to a very limited extent. This is particularly due to Sections 35,44,53 and 94 of the amended LAs Act (Act No. 23 of 1992) that empowers LAs to facilitate and aid FDIs by providing them with land, water, electricity and waste management services [9].…”
Section: Introductionmentioning
confidence: 99%
“…Their study observed that FDI exerts both direct and indirect positive effects on economic growth. LE, et al [41] applied provincial data, from 1997 to 2019 in Vietnam, using the vector autoregression (VAR) and ARDL estimators and found that economic growth positively influences economic growth, but FDI does not influence economic growth. On the contrary, Joshua [42] applied the ARDL approach to examine the nexus between FDI and economic growth in Nigeria, from 1981 to 2016, and found that FDI exerts a positive but insignificant effect on economic growth in both the long and short runs.…”
Section: Empirical Insights Between the Fdi And Economic Growth Nexusmentioning
confidence: 99%